National Culture as an Effort to Maintain National Resilience in the Era of Globalization - Zetty Selfia Putri Widodo; Sofi Isnaini (Konsultan Jurnal Ilmiah Indonesia, 2025)
Globalization has brought significant changes to Indonesia’s national culture through technological development, information flow, and increasingly intensive cross-cultural interactions. These changes directly impact cultural values, particularly weakening collectivist orientation, reducing younger generations’ interest in local traditions, and increasing the dominance of global popular culture, which can potentially erode national identity. This study aims to analyze the role of national culture in maintaining national resilience amid globalization pressures, as well as to identify strategies for strengthening it through education and social policies. The method employed is a literature review of forty-one national and international scholarly articles published between 2020 and 2025. The results show that national culture serves as a strategic instrument in maintaining social cohesion, reinforcing national identity, and preventing social disintegration through strengthening Pancasila values, revitalizing local wisdom, utilizing digital media for cultural preservation, and implementing inclusive social policies. Integration of character education, cultural policies, and community participation proves effective in enhancing national resilience. Thus, national culture functions not only as a heritage but also as a dynamic foundation for nation-building in the era of globalization.